1994
DOI: 10.1111/j.1095-8649.1994.tb01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct estimates of multi‐mesh gillnet selectivity to Oreochromis shiranus chilwae

Abstract: The selectivity of multi‐mesh monofilament nylon gillnets to Oreochromis shiranus chilwae was estimated directly by gillnetting in a small reservoir containing a population marked by size class. Numbers in each size class were estimated using the adjusted Petersen estimate. Pearson Type I curves were fitted to plots of selectivity against the fish length/mesh perimeter ratio, for two modes of capture: wedging and tangling. The generality of the selectivity curves is tested and discussed. The tangling component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Hamley (1980) pointed out that perch are easily tangled and roach are usually only wedged or gilled. Our percids were more frequently gilled and tangled than cyprinids, but still the majority of all species were wedged, which is in accordance with the results of other studies (Winters and Wheeler, 1990;Henderson and Wong, 1991;Mattson, 1994;Santos et al, 1995;Hansen et al, 1997;Reis and Pawson, 1999;Yokota et al, 2001;Grant et al, 2004). Due to the low number of percids that were tangled, and the similar proportions of percids and cyprinids that were gilled, it could be concluded that the mechanism of enmeshing cannot importantly bias the gillnet catches towards a higher proportion of percid species in the reservoirs studied.…”
Section: Discussionsupporting
confidence: 92%
“…Hamley (1980) pointed out that perch are easily tangled and roach are usually only wedged or gilled. Our percids were more frequently gilled and tangled than cyprinids, but still the majority of all species were wedged, which is in accordance with the results of other studies (Winters and Wheeler, 1990;Henderson and Wong, 1991;Mattson, 1994;Santos et al, 1995;Hansen et al, 1997;Reis and Pawson, 1999;Yokota et al, 2001;Grant et al, 2004). Due to the low number of percids that were tangled, and the similar proportions of percids and cyprinids that were gilled, it could be concluded that the mechanism of enmeshing cannot importantly bias the gillnet catches towards a higher proportion of percid species in the reservoirs studied.…”
Section: Discussionsupporting
confidence: 92%
“…In theory, this should guarantee that the catchability of fish does not change when the fish size increases." However, many authors, as well as this study have shown that catchability (∼height of the selectivity curve) increased with the mesh/fish size (Mattson, 1994;Santos et al, 1995;Jensen, 1995a,b;Jensen and Hesthagen, 1996;Santos et al, 1998;Kurkilahti et al, 1998). This is related to the higher probability that larger fish will encounter the gillnet.…”
Section: Discussionmentioning
confidence: 59%
“…A multi‐mesh gillnet (5–43 mm mesh size) was used in this study and sampling sites were selected where impacts of gear selectivity were thought to be minimal. While gillnets can be very selective for size and species (Mattson, 1994; van der Mheen, 1995), selectivity was most likely reduced by using the multi‐mesh gillnet with a wide range of mesh sizes. Net location can also affect gear selectivity.…”
Section: Discussionmentioning
confidence: 99%